Extracts of Codiaeum variegatum (L.) A. Juss is Cytotoxic on Human Leukemic, Breast and Prostate Cancer Cell Lines - Mathias Tawiah Anim, Christopher Larbie, Regina Appiah-Opong, Isaac Tuffour, Kofi Baffour-Awuah Owusu, Abigail Aning (Journal of Applied Pharmaceutical Science, 2016)
The high cost of treatment of cancer coupled with the emergence of drug resistance makes it imperative for new drug interventions to curb its occurrence. Hence, the objective of this research was to determine the phytochemical, total phenolic content, antioxidant and antiproliferative effect of Codiaeum variegatum crude extracts and fractions. The MTT cell viability and DPPH assays among others were used to determine the selected properties of the plants. The presence of general glycosides, tannins, alkaloids, flavonoids and sterols was observed in its stem bark and leaf. Triterpenoids were present in the leaf only while saponins were observed in the stem bark only. Strong antioxidant activities were observed in both stem bark and leaf with EC50 values of 0.053±0.004 mg/mL and 1.396±0.073 mg/mL respectively. Both crude extracts showed antiproliferative activity towards all cancer cell lines with the stem bark exhibiting the strongest cytotoxicity. However, both showed strong cytotoxicity towards normal cells as well. The mechanism of cell death was determined to be apoptosis. Further testing of fractions from the stem bark crude extract revealed an increase in cytotoxicity of its chloroform fraction against Jurkat cells with an IC50 of 44.71±0.44 µg/mL. These results establish the antiproliferative nature of this plant.
Keywords: Antiproliferative, Codiaeum variegatum, apoptosis, cytotoxicity, fractionation, antioxidant.